GAMBARAN DISPEPSIA PADA MAHASISWA FAKULTAS KEPERAWATAN UNIVERSITAS RIAU - Yeni Rahmah; Reni Zulfitri; Widia Lestari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
Health problems that are common and often experienced by many people, one of which is dyspepsia. Dyspepsia is a term used for a syndrome or collection of syndromes consisting of pain or discomfort in the epigastrium, nausea, vomiting, bloating, early satiety, feeling full, and belching. This study aims to describe the incidence of dyspepsia in university students in Riau. The research design used is descriptive. The sample in this study was 215 patients using stratified random sampling technique. The data retrieval tool used was a questionnaire which was tested for validation and reliability. Analysis of the data used is univariate. Showed that the gender was female (93.0%), Minang ethnic (34.4%), class of 2017 students (21.8%), dyspepsia symptoms quickly satiety with irregular eating patterns (45.5%), symptoms of dyspepsia quickly filled with irritating types of food and drink (45.1%), 1000 students have experienced symptoms of early satiety (55.3%) while for the incidence of dyspepsia with dyspepsia (75.3%). It is recommended for students to maintain regular eating patterns and regularly consume lots of healthy and non-irritating food and drinks, so that it can cause dyspepsia in students. Eating patterns and types of food and beverages have a significant relationship with the incidence of dyspepsia in students. Keywords: Dyspepsia, diet, types of food and drink and students